Komposisi ukuran dan pola pertumbuhan ikan baronang lingkis Siganus canaliculatus di Perairan Kwatisore, Kabupaten Nabire - Musyeri, Philipus; Manangkalangi, Emmanuel; Sembel, Luky; Toha, Abdul Hamid A.; Tebaiy, Selvi (Program Pascasarjana Universitas Papua, 2025)
ABSTRACT: The rabbitfish, Siganus canaliculatus is one of the components in the coastal waters ecosystem (mangrove, seagrass, and coral reef) and also has important economic value for coastal communities, but information is still limited, especially in Papuan waters. This study aims to analyze the size composition and growth patterns of rabbitfish (Siganus canaliculatus) based on habitat differences in the waters of Kwatisore, Yaur District, Nabire Regency. Sampling was carried out at three locations representing various habitat types, such as mangrove, seagrass, and coral reef. The data collected included the total length (mm) and body weight (g) of the fish, which were then analyzed using the length-weight relationship model W = aLb. The results showed that the average body length and average body weight were greater in the coral reef habitat type, but relatively the same among the three research locations. The overall growth pattern (habitat type and location) with a tendency for body length to increase faster than body weight (negative allometric pattern) with a b value ranging from 2.771 to 2.888. The size and growth patterns obtained in this study indicate connectivity between locations and habitats, although both habitat types show different roles in the life cycle of this fish. This study provides important information for ecosystem-based management of the rabbitfish resource in the coastal area of Nabire.